WHO SHOULD LEAD DIVERSITY & INCLUSION EFFORTS? NOT WHO YOU THINK. Issue 106 (20th September 2022) - Rodgers, James O.
Abstract: Rodgers says that the most important elements of effective leadership are clarity and vulnerability. He further says that he defines leadership as "selling an idea, concept, or vision so that people willingly follow. When it comes to Diversity & Inclusion/D&I, leaders must be clear about what they see as possible and what they want for their followers. The problem seems to be that too few leaders have a clear concept of diversity and inclusion." He purposely does not use the term inclusion in this construct: "Notice that I use the term D&I (diversity and inclusion). I introduced the term diversity management in the early 2000s as an indication that D&I has the capacity to improve enterprise performance. I now encourage others to stick with the term D&I and avoid the perpetual language roulette (changing terms without changing outcomes) and word salad (equity [E], belonging [B], justice [J], acceptance [A], empathy [E], etc.). The temptation to change the language when progress is elusive must be resisted." In his words, D&I is a change effort that includes the following competencies, which in his words are Change management, Conceptual clarity, Relationship building, Leadership skills, Strategy and execution, Trust building, and Language skills.